DAMPAK ADOPSI KECERDASAN BUATAN TERHADAP KINERJA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) - Sucipto Basuki; Riyanto Riyanto; I Ketut Sudaryana; Jan Everhard Riwurohi (ISTEK WIDURI, 2026)
The advancement of Artificial Intelligence (AI) has significantly accelerated digital transformation across various sectors, particularly Micro, Small, and Medium Enterprises (MSMEs). This Research aims to investigate the effects of AI integration on the operational efficiency of MSMEs in the Cibitung District of Bekasi Regency. Empirical data were gathered through a survey of MSME stakeholders, using a meticulously structured questionnaire, and subsequently analyzed using data-driven methodologies within the Orange Data Mining application. The analytical process encompassed data preprocessing and correlation analysis. The results reveal a positive correlation between AI integration and MSME operational performance. A correlation coefficient of 0.726 indicates a robust positive association between AI adoption and MSME sales performance, whereas an R² of 52.7% indicates that the model exhibits moderate to good predictive capability in explaining variations in MSME performance. These findings suggest that adopting artificial intelligence can enhance operational efficiency, boost business productivity, and expand MSMEs’ market reach. This study enriches the existing literature by proposing an analytical framework grounded in Orange Data Mining as a viable alternative to conventional analytical methodologies in MSME Research, while simultaneously underscoring the practical implications for digital transformation strategies and policy formulation aimed at facilitating AI adoption within the MSME sector.